The relationship between planning and preparation, classroom environment, soft skills and teaching effectiveness at Dungun secondary schools / Nur Shafini Mohd Said ... [et al.] - Mohd Said, Nur Shafini; Md Khlapiah, Nur Syahida; Omar Ali, Siti Rapidah; Mat, Khalid Amin; Mansor, Farah Ahlami (Universiti Teknologi MARA, Perlis, 2021)
Most of an organization's problems are teaching effectiveness. This problem also occurred at one of the secondary schools in Dungun. For the different and different reasons and needs, it is not easy for the organization to solve the issue of effectiveness due to each teacher. The study examined the relationship between planning and preparation, classroom environment and soft skills towards teaching effectiveness in the Dungun Secondary School. For this study, the researcher set the Dungun Secondary School as the population studied by 90 teachers. A set of questionnaires was used as the main instrument for data collection. The convenience sampling was selected from teachers Dungun Secondary School for this study. This is because the method for the sampling design was the most efficient. In addition, the method is easily understood and results for the entire population are projected. After several follow-ups, a total of 73 questionnaires was received. The Pearson correlation coefficient was used to classify factors that affect the teaching effectiveness of Dungun Secondary School. Statistically, the Statistical Package for Social Science (SPSS) was used for data analysis. The hypothesis was accepted based on the findings. In order to help teachers recognize their weaknesses, the training of teachers should be improved so that they can not only learn but also increase their teaching effectiveness. The researcher hopes that the results will also benefit the organization.